A feasibility study on green energy production at the location of offshore oil and gas platforms in Australia - Aryai, Vahid; Abdussamie, Nagi; Abbassi, Rouzbeh; Penesis, Irene; Wang, Chien-Ming; Garaniya, Vikram (Volume 10: Professor Ian Young Honouring Symposium on Global Ocean Wind and Wave Climate; Blue Economy Symposium; Small Maritime Nations Symposium, 2023)
An important aim of the offshore energy sector is to replace oil and gas production with sustainable and environmentally friendly energy production. The public expectations and the international environmental agreements enforced all sectors of the governments to encourage the transition from fossil fuel production to renewable energy production. Green energy production alternatives by transforming/repurposing available offshore oil and gas platforms in Australia is essential for a successful blue economy. This research aims to explore the potential for generating green energy at the location of offshore oil and gas platforms that exist in different oil and gas basins around Australia. To this aim, the locations of seven platforms, one from each basin, are selected as case studies, and the potential energy production by using wind, wave, and solar energy conversion systems in the vicinity of the existing platforms is estimated. Furthermore, the green hydrogen production alternative is investigated in the case of repurposing the existing platforms as a storage, distribution and export multipurpose offshore platform. Finally, discussions on the other requirements for selecting target options for repurposing offshore oil and gas platforms are presented.